2014
DOI: 10.3389/fphys.2014.00117
|View full text |Cite
|
Sign up to set email alerts
|

Building a brain under nutritional restriction: insights on sparing and plasticity from Drosophila studies

Abstract: While the growth of the developing brain is known to be well-protected compared to other organs in the face of nutrient restriction (NR), careful analysis has revealed a range of structural alterations and long-term neurological defects. Yet, despite intensive studies, little is known about the basic principles that govern brain development under nutrient deprivation. For over 20 years, Drosophila has proved to be a useful model for investigating how a functional nervous system develops from a restricted numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
47
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 44 publications
2
47
0
Order By: Relevance
“…In contrast to proliferative cells, such as neural stem cells (Lanet & Maurange ), relatively little is known about how growth of postmitotic and morphologically complex cells is influenced by nutritional status, and whether observed nutrient‐dependent changes are physiologically relevant or not. Recent studies that address this question include investigations of tracheal terminal cells that innervate the midgut (Linneweber et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to proliferative cells, such as neural stem cells (Lanet & Maurange ), relatively little is known about how growth of postmitotic and morphologically complex cells is influenced by nutritional status, and whether observed nutrient‐dependent changes are physiologically relevant or not. Recent studies that address this question include investigations of tracheal terminal cells that innervate the midgut (Linneweber et al .…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to proliferative cells, such as neural stem cells (Lanet & Maurange 2014), relatively little is known about how growth of postmitotic and morphologically complex cells is influenced by nutritional status, and whether observed nutrient-dependent changes are physiologically relevant or not. Recent studies that address this question include investigations of tracheal terminal cells that innervate the midgut (Linneweber et al 2014), a subset of serotonergic neurons that innervate the prothoracic gland (Shimada-Niwa & Niwa 2014), and a family of Drosophila somatosensory neurons, dendritic arborization (da) neurons (Shimono et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Part of this NE, named the outer proliferation center (OPC), will be converted into short--lived NBs that will generate the neurons of the medulla (Egger et al, 2007;Lanet et al, 2013;Yasugi et al, 2008). The NE--to--NB conversion in the OPC is initiated around mid--L3 by high levels of ecdysone produced by the ring gland after the larva reaches a critical weight (Lanet et al, 2013;Lanet and Maurange, 2014). Indeed, in addition to commit larvae to metamorphosis, ecdysone in the brain triggers the rapid progression of a differentiation wave throughout the NE, allowing the rapid differentiation of all NE cells into NBs (Lanet et al, 2013;Yasugi et al, 2010;Yasugi et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Studies on Drosophila have generated valuable insight into how stem cells are controlled by dietdependent pathways. Diverse adult stem cell populations respond to food supply/deprivation similarly (Chell and Brand, 2010;Ables and Drummond-Barbosa, 2011;Rafalski and Brunet, 2011;Sp eder et al, 2011Sousa-Nunes et al, 2011Cheetham and Brand, 2013;Lanet and Maurange, 2014;Liu et al, 2014). For example, ND promotes stem and progenitor cell differentiation in the germline (Hsu and Drummond-Barbosa, 2009) and the lymph gland (Benmimoun et al, 2012;Shim et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Feeding induces quiescent neuroblasts to re-enter the cell cycle (Chell and Brand, 2010;Sousa-Nunes et al, 2011). In response to ND, many tissues undergo a decline in both cell proliferation and growth rate leading to undersized adults (Lanet and Maurange, 2014). Recently, Love et al (2014) showed how ND affects stem and progenitor cells in the ciliary marginal zone of the zebrafish and Xenopus retina.…”
Section: Introductionmentioning
confidence: 99%